2007
DOI: 10.2298/aoo0704094z
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic argon plasma coagulation for the management of solid, centrally located lung cancer

Abstract: Argon plasma coagulation (APC) is one of the interventional pulmonology techniques primarily aimed at the treatment of hemoptysis. It represents a form of non contact electrosurgey that uses ionized argon gas in order to produce electrical current that affects soft tissues. APC is reported to be effective in the treatment of early stage lung cancer, in the treatment of benign granulation tissue surrounding tracheal stents and in palliative treatment of malignant airway obstruction. Major indication for APC is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
0
2
0
2
Order By: Relevance
“…Эндопротезирование трахеи и крупных бронхов выполнимо далеко не всегда, тре-бует наличия недешевых стентов разного диаметра и длины [13,14]. Аргоноплазменная коагуляция сопровождается очень медленной деструкцией опухолевых масс и для реканализации при протяженных стенозах применима мало [8,9,15].…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Эндопротезирование трахеи и крупных бронхов выполнимо далеко не всегда, тре-бует наличия недешевых стентов разного диаметра и длины [13,14]. Аргоноплазменная коагуляция сопровождается очень медленной деструкцией опухолевых масс и для реканализации при протяженных стенозах применима мало [8,9,15].…”
Section: Discussionunclassified
“…Авторами предложено проводить лазерное воздействие в среде газа, не поддерживающего горение, например аргона, а также разработано устройство для реализации метода. Путем ряда экспериментальных исследований выбраны наиболее удобные параметры лазерного воздействия, а также скорость подачи аргона [5,8,9]. В клинической практике эндоскопическое облучение опухолевой ткани проводили лазерным излучением с длиной волны 1060 нм, при этом в зону лазерного воздействия подавалась струя аргона с интенсивностью подачи 0,6-1,6 л/мин, а облучение стенозирующего образования проводили при плотности мощности 15-18 Вт/см 2 .…”
Section: материал и методыunclassified
“…7,14,15,17,21,22,[34][35][36][37] Reichle et al reported that the APC complication ratio was 3.7%. 30 Shaw, et al and Reddy et al reported a case of cerebral gas embolisation that occurred during bronchoscopic APC.…”
Section: Discussionmentioning
confidence: 99%
“…[5–11] All of the major interventional pulmonology guidelines are suggesting that Nd:YAG laser resection should be considered a part of multimodality treatment of advanced central lung cancer with endobronchial obstruction. [1219] Nd:YAG laser resection alone or in combination with other interventional techniques demonstrated benefit in treatment of inoperable early stage lung cancer, in the treatment of benign CAO, and in multimodality treatment of central, advanced stage lung cancer. [20–27]…”
mentioning
confidence: 99%